2013
DOI: 10.1590/s0080-62342013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Carga de trabajo en tres grupos de pacientes de UCI Española según el Nursing Activities Score

Abstract: RESUmoO objetivo deste estudo é avaliar a carga de trabalho na admissão e alta dos pacientes em três grupos (síndrome coronária aguda, insuficiência respiratória aguda e sepsis) em cuidados intensivos. Trata-se de um estudo prospectivo, descritivo, que decorreu durante 27 meses, incluindo 563 pacientes. Para a avaliação da carga de trabalho utilizou-se a escala Nursing Activities Score. A partir dos resultados do estudo parecem existir diferenças significativas na carga de trabalho no dia da admissão e alta en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
3
2
1
3
Order By: Relevance
“…Based on the present findings, the mean daily NAS score was 65.32%, indicating high levels of required patient care and nursing workload in the ICU. The mean NAS scores in some different studies conducted in ICUs were almost similar to the present results (11,15). On the other hand, the NAS score was reported to be 47% in a study by Reich et al (2014) in a CCU and 34.9% by Panunto et al (2015) in a gastroenterology unit (21,22).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Based on the present findings, the mean daily NAS score was 65.32%, indicating high levels of required patient care and nursing workload in the ICU. The mean NAS scores in some different studies conducted in ICUs were almost similar to the present results (11,15). On the other hand, the NAS score was reported to be 47% in a study by Reich et al (2014) in a CCU and 34.9% by Panunto et al (2015) in a gastroenterology unit (21,22).…”
Section: Discussionsupporting
confidence: 89%
“…Since the evaluated hospital unit contained 9 beds, 92.7% of the beds were always occupied, which exceeds the bed occupancy rate reported in other similar studies (11,15). Based on the present findings, the mean daily NAS score was 65.32%, indicating high levels of required patient care and nursing workload in the ICU.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The analysis of demographic and clinical characteristics revealed that age (14,15) , origin (11,17) , type of hospital stay (18) , length of stay (11,14) , and mortality (11,15) in the present study corroborate national and international literature. Divergent results were found regarding gender (11,17) , which reinforces the idea that women seek healthcare services more often, including in the oncological area.…”
Section: Discussionsupporting
confidence: 88%
“…La relación entre la adecuada dotación del personal de enfermería en los servicios de hospitalización y los resultados en términos de calidad (mortalidad, complicaciones) y eficiencia (estancia hospitalaria), están ampliamente contrastadas 8 . Una adecuada proporción de profesionales de enfermería en relación al tipo de pacientes ingresados, una distribución de tiempo adecuado en las actividades directas, indirectas y asociadas que realiza en bien del paciente va a tener un efecto positivo, consiguiéndose una disminución en la aparición de infecciones nosocomiales, monitorio exhaustivo por paciente, en la duración de la estancia en la unidad y en la satisfacción del paciente 9 .…”
Section: Introductionunclassified